"It's just reflex now": German Language Learners' Use of Online Resources. Issue 1 (19th May 2013) - Larson‐Guenette, Julie
Abstract This study examined how often and to what extent university learners of German use online resources (e.g., online dictionaries and translators) in relation to German coursework, their motivations for use, and their beliefs about online resources and language learning. Data for this study consisted of open‐ended surveys (n=71) and face‐to‐face interviews (n=13) with students from second‐, fourth‐, fifth‐, and sixth‐semester language courses. Results from both the survey and interview data revealed that learners consistently used online resources, including online dictionaries, translation sites, and other websites for reasons related to time efficiency, vocabulary, to "check" or "compare" their work, and general reference. As to whether or not the use of online resources contributes to learning, learners had mixed beliefs regarding the advantages and disadvantages of using online resources.